Role of lateral amygdala calstabin2 in regulation of fear memory - Ren-wen Han; Zhi-peng Liu; Hong-ru Lin; Ao-wen Tian; Yun-fei Xiao; Jie Wei; Ke-yu Deng; Bing-xing Pan; Hong-bo Xin (Molecular Brain, 2020)
Abstract Calstabin2, also named FK506 binding protein 12.6 (FKBP12.6), is a subunit of ryanodine receptor subtype 2 (RyR2) macromolecular complex, an intracellular calcium channel. Studies from our and other’s lab have shown that hippocampal calstabin2 regulates spatial memory. Calstabin2 and RyR2 are widely distributed in the brain, including the amygdala, a key brain area involved in the regulation of emotion including fear. Little is known about the role of calstabin2 in fear memory. Here, we found that genetic deletion of calstabin2 impaired long-term memory in cued fear conditioning test. Knockdown calstabin2 in the lateral amygdala (LA) by viral vector also impaired long-term cued fear memory expression. Furthermore, calstabin2 knockout reduced long-term potentiation (LTP) at both cortical and thalamic inputs to the LA. In conclusion, our present data indicate that calstabin2 in the LA plays a crucial role in the regulating of emotional memory.